JP‐45/JSRP1 Variants Affect Skeletal Muscle Excitation–Contraction Coupling by Decreasing the Sensitivity of the Dihydropyridine Receptor. Issue 1 (11th October 2012) - Yasuda, Toshimichi; Delbono, Osvaldo; Wang, Zhong‐Min; Messi, Maria L.; Girard, Thierry; Urwyler, Albert; Treves, Susan; Zorzato, Francesco
ABSTRACT JP‐45 (also JP45; encoded by JSRP1) is an integral protein constituent of the skeletal muscle sarcoplasmic reticulum junctional face membrane interacting with Cav1.1 (the α.1 subunit of the voltage‐sensing dihydropyridine receptor, DHPR) and the luminal calcium‐binding protein calsequestrin. Two JSRP1 variants have been found in the human population: c.323C>T (p.P108L) in exon 5 and c.449G>C (p.G150A) in exon 6, but nothing is known concerning the incidence of these polymorphisms in the general population or in patients with neuromuscular diseases nor the impact of the polymorphisms on excitation–contraction (EC) coupling. In the present report, we investigated the frequencies of these two JSRP1 polymorphisms in the Swiss malignant hyperthermia population and studied the functional impact of the variants on EC coupling. Our results show that the polymorphisms are equally distributed among malignant hyperthermia negative, malignant hyperthermia equivocal, and malignant hyperthermia susceptible individuals. Interestingly, however, the presence of either one of these JP‐45 variants decreased the sensitivity of the DHPR to activation. The presence of a JSRP1 variant may explain the variable phenotype seen in patients with malignant hyperthermia carrying the same mutation and, more importantly, may counteract the hypersensitivity of EC coupling caused by mutations in the RYR1 gene.